Customer Satisfaction And Loyalty On Factory Automation Product In Malaysia - Oo, Bryant Yong Siang (2009)
This research aims to assist suppliers involved in the factory automation industry to gain insights into the needs and wants of their customers by accessing the variables in the marketing mix such as Price, Product, Service, Sales force that will affect the loyalty and the satisfaction of the buyers.